Malignant Transformation of Primary Acquired Melanosis into Conjunctival Melanoma in an Adolescent Male: A Clinico-Pathological Case Report and Management Review - Fitrah; Ardizal Rahman; Mardijas Efendi (HM Publisher, 2025)
Background: Conjunctival malignant melanoma (CMM) is a rare but potentially lethal ocular surface malignancy, especially uncommon in adolescents. It often arises from a precursor lesion known as primary acquired melanosis (PAM) with atypia. We present a case of CMM developing from long-standing PAM in an 18-year-old male, highlighting the diagnostic and therapeutic challenges in this unusual demographic. Case presentation: An 18-year-old male presented with a pigmented conjunctival lesion in his right eye, which had been present for over a decade but had recently shown progressive enlargement and darkening. Slit-lamp biomicroscopy revealed a 5x2 mm, variegated, hyperpigmented lesion on the bulbar conjunctiva with a prominent feeding vessel. The patient underwent an excisional biopsy using a